ANALISIS PERUBAHAN EKSTERNAL DALAM PENGEMBANGAN KAWASAN WISATA BAHARI KEPULAUAN SAPEKEN MADURA - Muchammad Nurif; Endang Sulastri (Institut Teknologi Sepuluh Nopember, 2017)
To market the potential of marine and tourism, especially marine tourismrequired an appropriate marketing model for an optimal result. Given thearea of Sapeken Island adjacent to P.Bali which is the icon of Indonesiantourism, the prospects of tourism development, including marine tourism, isvery good that is by attracting tourists both domestic tourists and foreigntourists to continue the tour from P.Bali to the Sapeken Islands..The rebuilding of Trunojoyo airport in Sumenep regency to be operatedcommercially will facilitate tourist access to visit Sumenep regency and thento Sapeken Islands because in Sapeken sub-district is P.Saor Desa Sapeken,P.Pagerungan Besar (former Pertamina).By knowing the potential in Sapeken region, including the potential of marinetourism spread across several small islands, and the role of tourism sector inmoving the economy of a region, it is necessary to find a strategy or model tomarket these potentials in the package.